Primeness and Primitivity Conditions for Twisted Group C^*-Algebras - Omland, Tron Ånen (MATHEMATICA SCANDINAVICA, 2014)
For a multiplier (2-cocycle) σ on a discrete group G we give conditions for which the twisted group C^*-algebra associated with the pair (G,σ) is prime or primitive. We also discuss how these conditions behave on direct products and free products of groups.